Inovasi Pengembangan Kurikulum Sekolah Berbasis Pesantren dalam Meningkatkan Kepercayaan Masyarakat - Muhammad Munif; Fathor Rozi; Moh. Aminullah (MANAZHIM, 2021)
This study aims to find out innovations in developing a pesantren-based school curriculum in increasing public confidence in SMP Islam Sumberranyar Paiton Probolinggo. This research uses a qualitative approach, while the type of research used is a case study. The results of the study show that: innovations in developing pesantren-based school curriculum in increasing public trust are as follows; The innovation of developing a pesantren-based school curriculum in Islamic junior high schools has improved very well, from the development of the school curriculum trying to develop a pesantren curriculum by changing the learning system, the supporting factors for innovation in developing a pesantren-based school curriculum in Islamic junior high schools include the principal involving all relevant stakeholders, both administrators and administrators. The entire board of teachers, community leaders, guardians of students as well as support from boarding school caregivers, inhibiting factors for innovation in developing a pesantren-based school curriculum in Islamic junior high schools, the low awareness of teachers to develop learning tools, this hampers the innovation of developing a pesantren-based school curriculum which was developed together at Sumberanyar Islamic Middle School Paiton, while the positive impact of curriculum innovation developed at Islamic Junior High School can increase public confidence in Sumberanyar Islamic Junior High School Paiton Probolinggo